Sharia Financial Technology in the Distribution of People's Business Credit Program Funds for Micro, Small, and Medium Enterprises - Mahendra , Gema Aditya; Nurjaya, Nurjaya; Alkhair, Rayyan; Aminuddin, Mohammad (Green Publisher, 2022)
This study analyzes the presence of Islamic Fintech as a sharia-based digital financial institution as a role in distributing People's Business Credit (KUR) from banks to Micro, Small and Medium Enterprises (MSMEs). The research method used in this study is a qualitative method using secondary data with deductive analysis. The results of this study indicate the potential and role of Sharia Fintech in distributing KUR by banks to MSMEs. The existence of sharia fintech is expected to increase the productivity of MSMEs in Indonesia.